Optimization of piroxicam tablet formula using flowlac, avicel and compritol by Simplex Lattice Design Method - Suhesti, Tuti (Indonesian Journal of Pharmacy, 2009)
Piroksikam is non steroid anti inflammation drug (NSAID) with small dose (10-20 mg daily) with a long time (t1/2) elimination. Piroxicam formulation was expected able to yield a good (quality) tablet to physical characteristic standard. Tablet r component was consisted of Flowlac 100 (filler), Avicel PH-101 (binder) and Compritol 888 ATO (lubricant).The research was done with simplex lattice design (SLD) by using 3 component, i.e. Flowlac (A), Avicel (B), and Compritol (C). Seven formula were needed, I,e, F1 (100 % A), F2 (100 % B), F3 (100 % C), F4 (50 % A and 50 % B), F5 (50 % B and 50 % C), F6 (50 % A and 50 % C),dan F7 (33.33% A, 33.33 % B, 33.33 % C). The optimization parameters of piroxicam tablets were flow rate of the tablet mass, tablet hardness, disintegration time, piroxicam content and the dissolution (C45), on SLD model; equations, contour plots, and superimposed of contour plots were obtained, by which the optimum formula was determined.Based on superimposed contour plot optimum formula was obtained with proportion of Flowlac (89.6 %), Avicel (7.4 %) and Compritol (3 %). The result of flowability was 21.46 g/second; hardness (6.46 kg); disintegration time (6.98 minutes); drug content (10.13 mg) and dissolution C45 (7.35 mg) Interaction of Flowlac-Avicel-Compritol could influence the physical properties and the release profile of tablet. Flowlac was the most dominant factor in increasing flowability, hardness and dissolution of tablet. Compritol was the most dominant factor in increating time of disintegration tablet.Key words: optimization; piroxicam; simplex lattice design.